The Development of the Malaysian Technology Content Framework towards the Establishment of the Malaysian Technology Index in Manufacturing Industry - Abdullah, Ibrahim; Siti Aishah, Md Hasan (2015)
Appropriate technology plays a vital role in the ability of manufacturing enterprises to be productive and competitive. Today, most companies accept the fact that they must acquire relevant technology to strengthen their technological capabilities and core competencies. The proposed study intends to investigate the content of technology in that affect the application of new technology in Malaysian manufacturing industry. Next, this study aims to develop the Malaysian Technology Content Framework, in which this framework will form the basis for the development of Malaysian Technology Index for manufacturing industry. This study is carried out through three phases which involves survey of literature and practices, interviews or participatory dialogue with industry players, and pilot testing. This study indicates that all technology contents correlated with the technology strategy that will lead to the application of new technology.